Medical implants by using RP and investment casting technologies - Milan Horacek; Ondrej Charvat; Tomas Pavelka (China Foundry, 2011)
The paper deals with the production technology of knee joint replacement by using rapid prototyping technology. The aim of the work is to outline the manufacturing technology intended for prototype production with the use of rapid prototyping and investment casting technology for use in orthopaedics and the surgery of knee joint replacement. The research results should make an effective contribution in the attempts to minimize the invasive surgical procedure, shorten the production of knee joint replacement as well as reduce the cost. At present, the research is focused on the preparation of STL data from CT (Computed Tomography) and verification of the production technology of prototypes made using available RP technology and its evaluation.